Ultrasound-Guided Reduction of Distal Radius Fractures - Anita Sabzghabaei; Majid Shojaee; Ali Arhami Dolatabadi; Mohammad Manouchehrifar; Mahdi Asadi (Archives of Academic Emergency Medicine, 2018)
Introduction: Distal radius fractures are a common traumatic injury, particularly in the elderly population. In the present study we examined the effectiveness of ultrasound guidance in the reduction of distal radius fractures in adult patients presenting to emergency department (ED). Methods: In this prospective case control study, eligible patients were adults older than 18 years who presented to the ED with distal radius fractures. 130 consecutive patient consisted of two group of Sixty-Five patients were prospectively enrolled for around 1 years. The first group underwent ultrasound-guided reduction and the second (control group) underwent blind reduction. All procedures were performed by two trained emergency residents under supervision of senior emergency physicians. Results: Baseline characteristics between two groups were similar. The rate of repeat reduction was reduced in the ultrasound group (9.2% vs 24.6%; P = .019). The post reduction radiographic indices were similar between the two groups, although the ultrasound group had improved volar tilt (mean, 7.6° vs 3.7°; P = .000). The operative rate was reduced in the ultrasound groups (10.8% vs 27.7%; P = .014). Conclusion: Ultrasound guidance is effective and recommended for routine use in the reduction of distal radius fractures.